(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2023)
The Litaniae lauretanae (the Litany of Loreto), a Marian litany with medieval roots, has been set numerous times in polyphony, as well as in grand settings with soloists and orchestra, to be performed all over Catholic Europe. Famous musicians who composed settings of the Litany of Loreto include Orlando di Lasso, Giovanni Pierluigi da Palestrina, Claudio Monteverdi, Heinrich Biber, and Wolfgang Amadeus Mozart. This article discusses Mozart’s two settings of the Litaniae lauretanae that were composed in May 1771 and in 1774. The analysis of parts of Mozart’s settings in the light of the historical background of Loreto pilgrimages and the litany’s ritual and musical uses highlights some of their remarkable musical features. It is argued that Mozart’s settings, more than any other major contemporary ones, constitute musical reenactments of ritual experience.